The introduction in Spain of educational policies based on a “business” oriented style of schools’ management: The case of Andalucía - Merchán, F. Javier (Education Policy Analysis Archives, 2012)
Since Margaret Thatcher’s government in Great Britain, educational policies based on a business oriented style of management of education have been imposed in many countries all over the world. This article focuses on two key aspects of this process. First, it makes some considerations on the foundations on which these policies rest, as well as on the effects that they are having in the functioning of the educational system. Second, by studying the particular case of Andalusia, which pioneered the application of many of these new formulas, this articles discusses how these policies have been introduced in Spain.